First Type III Solar Radio Bursts of Solar Cycle 25 - Kallunki, Juha; McKay, Derek; Tornikoski, Merja (Solar Physics, 2021)
Abstract The minimum of the previous solar cycle, Solar Cycle 24, occurred in December 2019, which also marked the start of the new Solar Cycle 25. The first radio bursts of the new solar cycle were observed in the spring season 2020. In this work we will present three type III solar bursts which were observed in May and June 2020 at radio frequencies between 18 – 90 MHz. There are two radio observatories in Finland that are capable of doing low-frequency solar radio observations: Aalto University Metsähovi Radio Observatory (MRO) and Kilpisjärvi Atmospheric Imaging Receiver Array (KAIRA) of the Sodankylä Geophysical Observatory, University of Oulu. The instruments of the two institutes have different design and characteristics, and they operate in rather different radio interference environments. We will compare simultaneous observations from these two instruments and we will also discuss the properties of these type III solar bursts.